HUBUNGAN PENGUATAN YANG DIBERIKAN OLEH GURU MATA PELAJARAN DALAM BELAJAR DENGAN KEPERCAYAAN DIRI PESERTA DIDIK DI SMA BUNDA PADANG - Pinalusa, Dedi; Kasih, Fitria; Zaini, Ahmad (Bimbingan dan Konseling, 2013)
This research bassed on the problem that had been found in location that hereare teachers who did not give reinforcement to the student. The purpose of this research is to recognize reinforcing relationship that is given by teacher in learning process with the confidence of student in SMA Bunda Padang. This kind of research correlation research. There are teacher who donât give reinforcement, uncare and donât pay enough attention to their student, student rarely answer the question that is asked by the teacher, there are student who has lack of confidence in studying. The population in this research is 214 and the sample that is observed as many as 54 people. The dataÂ  that is used in this research is interval data. To analyze the data, the Person Product Moment. The result of this research shows that there is significant relationship between reinforcement that is given by the teacher in learning process with the confidence of student in SMA Bunda Padang with score of r= 0,395. Conclusion: the relationship that is happen between both variable is positive correlation, which mean the bigger reinforcement, the higher level of the self confidence of student. The author suggest to the teacher to give reinforcement and help raising the self confidence of student in learning process.